Fostering Bilateral Ties: Exploring Paradiplomacy in the Sister City Collaboration between Padang and Ba Ria Vung Tau - Aprilian, Adinda Daffa; Azizah , Fatihatur Rahmi (Journal of Paradiplomacy and City Networks, 2023)
Padang, situated on the west coast of West Sumatra, serves as the capital city of West Sumatra Province, renowned for its thriving industrial, trade, service sectors, and tourism. Owing to the diverse and unique characteristics of Padang, the city has established a Sister City collaboration with Ba Ria Vung Tau. The latter, having expressed keen interest in this partnership, engaged in fruitful negotiations with Padang's Mayor, culminating in the signing of a Memorandum of Understanding (MoU) on May 31, 2016. The primary motivation behind this collaboration is the striking geographical and demographic similarities between the two cities, as well as their shared potential for growth. This paper examines the establishment of Sister City cooperation within the framework of paradiplomacy, which seeks to forge cooperative ties between domestic and foreign regions.